2022
DOI: 10.3390/pharmaceutics14061223
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Drug-Loaded Liposomes with Multi-Inlet Vortex Mixers

Abstract: The multi-inlet vortex mixer (MIVM) has emerged as a novel bottom-up technology for solid nanoparticle preparation. However, its performance in liposome preparation remains unknown. Here, two key process parameters (aqueous/organic flow rate ratio (FRR) and total flow rate (TFR)) of MIVM were investigated for liposome preparation. For this study, two model drugs (lysozyme and erythromycin) were chosen for liposome encapsulation as the representative hydrophilic and hydrophobic drugs, respectively. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Notably, Zheng et al reported the same trend using erythromycin as the model compound for the hydrophobic drug. 30 The DL% showed a similar trend to that of the recovery% (Fig. 1(e)).…”
Section: Investigation Of the Physicochemical Properties Of The Ptx-l...supporting
confidence: 69%
“…Notably, Zheng et al reported the same trend using erythromycin as the model compound for the hydrophobic drug. 30 The DL% showed a similar trend to that of the recovery% (Fig. 1(e)).…”
Section: Investigation Of the Physicochemical Properties Of The Ptx-l...supporting
confidence: 69%
“…The process was highly repeatable, with minimal variation in mean diameter observed over 6 replicates for each liposome synthesis condition. The inverse relationship between FRR and vesicle size is consistent with liposome formation using both hydrodynamic flow focusing 29,39,41 and rapid micromixing [44][45][46][47]67 . However, the vortex focusing process was found to yield low polydispersity, with an average PDI value of 0.04 and nearly constant size variance over the full range of flow rate ratios (Fig.…”
Section: Liposome Synthesissupporting
confidence: 66%
“…In the cyclonic flow cell, stretching and folding of the fluid interface under the influence of the vortical flow field contributes to rapid mixing of the miscible aqueous and lipid streams 65 . This aspect of the mixing process is similar to other vortex mixers explored for liposome synthesis [66][67][68][69] , in which both lipid and buffer are injected tangentially into a mixing chamber to generate chaotic advection patterns in a manner similar to herringbone or toroidal micromixers. Compared with mixing by conventional ethanol injection 70 , vortex mixing can yield enhanced mixing rates and improved control over liposome size.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Recent investigations revealed the multi-inlet vortex mixer technology as a suitable method to reach liposomal ERY with sizes lower than 200 nm and an encapsulation efficiency around 35%. It was reported that this method allowed for a good control on liposome size and EE by simply tuning the aqueous/organic flow rate ratio and flow parameters [ 39 ].…”
Section: Vesiclesmentioning
confidence: 99%